Artificial Intelligence for a Smarter Future: Trends, Applications, and Research Directions - Zohaib Hassan Sain; Tri Pujiani; Ida Dian Sukmawati; Jaime Da Costa Lobo Soares (Universitas Harapan Bangsa, 2026)
Artificial Intelligence (AI) has emerged as the defining technological force of the twenty-first century, fundamentally transforming industries, reshaping scientific inquiry, and reconfiguring the boundaries of what machines can accomplish. This paper presents a comprehensive quantitative and qualitative review of AI's most recent advances, covering key paradigms including Natural Language Processing (NLP), deep learning, computer vision, reinforcement learning, generative AI, and federated learning. Methodologically, this study adopts a structured narrative review: 48 peer-reviewed articles and authoritative technical reports published between 2019 and 2024 were retrieved from Scopus, IEEE Xplore, Web of Science, the ACL Anthology, and arXiv, and then screened and synthesized thematically across six AI paradigms. A systematic analysis of benchmark performance data across leading AI models, including GPT-4, Gemini Ultra, and AlphaFold 2, demonstrates measurable progress in accuracy, efficiency, and versatility. This study further maps the critical challenges impeding AI's responsible deployment of AI: data bias, computational cost, lack of explainability, adversarial vulnerabilities, and regulatory fragmentation. Drawing on evidence from recent peer-reviewed literature and industry reports, we propose a structured roadmap for future research directions, including Artificial General Intelligence (AGI), Explainable AI (XAI), Green AI, quantum machine learning, and human-AI collaboration frameworks. Our analysis underscores the urgent need for interdisciplinary research, ethical governance, and sustainable AI design principles to ensure that AI development aligns with the long-term values and societal goals of humanity.